Shariah crowdfunding model for enterpreneurship development in Malaysia - Rahman, Maya Puspa Rahman (2019)
This research studies the real meaning of Shariah-compliant crowdfunding (SCF) and how it could benefit Muslim entrepreneurs particularly in Malaysia. The rise of equity-based crowdfunding is expected to offer a new gateway for Muslim entrepreneurs given its similarity with risk-sharing concept as per the Shariah principles. Malaysia is the first country in Southeast Asia to legislate and award equity-based crowdfunding licences in June 2015. Accordingly, this study aims to propose a Shariah-compliant equity-based crowdfunding (SCF) model and analyse the acceptance level of Muslim entrepreneurs to use it in raising new funds. Based on primary data collected on 411 Muslim entrepreneurs in Malaysia, this study analyse the data using Structural Equation Modelling by adapting Technology Acceptance Model. It is found that perceived usefulness and perceived ease of use have positive effect on behavioral intention to use the proposed SCF model. Similar significance and positive results are found between perceived usefulness and behavioral intention to use the proposed SCF model. Hence, it is concluded that the respondent’s perceptions on the usefulness and ease of use positively affect the behavioral intention of using the new model. This research makes three contributions to the existing literature. First, it is the first to highlight on the possibility of developing SCF model within the Malaysian financial ecosystem. Second, it provides evidence on Malaysian entrepreneurs' understanding on crowdfunding and their intention to use it for fund sourcing by adopting TAM and SEM. Third, it develops a hypothetical structure of SCF model for the development of entrepreneurs in Malaysia. Taking the lead in Shariah-compliant crowdfunding research, this paper aims to contribute to the blueprints for the market players and regulators with regard to offering of SCF particularly in Malaysia. Apart from that, a separate study on the understanding, role and perspectives on digital economy of the entrepreneurs was also undertaken, in view of the rising importance of digital economy in contributing to the growth of the Malaysian economy.